Studi Potensi Hara Makro Air Limbah Budidaya Lele Sebagai Bahan Baku Pupuk Organik - Andriyeni Andriyeni; Firman Firman; Nurseha Nurseha; Zulkhasyni Zulkhasyni (University of Prof. Dr. Hazairin, SH, 2017)
The study of catfish waste water macro nutrient potential was aimed to emphasize level of pH, nitrogen, phosphor, potasium, c-organic and C/N ratio in catfish waste water. Based on our research it was found that the level of pH was 7-8, N in liquid waste was 0.98-1.67% with an average of 1.32% and N in solid waste was 1.99 – 13.97 % with an average of 6.23 %, P in liquid waste was 1.89 – 3.40 % with an average of 2.64 % and P in solid waste was 4.10-4.69 % dengan rata-rata 4.46 % and Potassium in liquid waste was 0.01-1.03 % dengan rata-rata 0.35 % and Potassium in solid waste was 2.31-4.09 % dengan rata-rata 3.21 %. Furthermore, the level C-organic in liquid waste was 0.28-0.98 % with an average of 0.63 % and in solid waste 16.28 – 24.64 % with average 21.67%. In addition, C/N ratio in solid waste was about 1.71-12.38 % with average of 6.71%. The nutrient levels in liquid waste did not meet requirement of Indonesia Agricultural Ministry as liquid organic fertiliser, but pH level did. However, the nutrients in solid level did meet the requirement from the ministry number 70 year 2011 and meet the national standard SNI-19-7030-2004. Unfortunately, C/N ratio in both liquid and solid waste did not meet the requirement and SNI standard.